(untitled) (Journal of the College of Basic Education, 2023)
The study aimed to identify (the necessary teaching competencies for first-grade teachers from their point of view). The research sample consisted of (50) male and female teachers from the Second Rusafa Education Directorate in Baghdad who teach the first three grades of the primary stage, and the research tool was a questionnaire consisting of (34) items distributed over three areas: Competencies related to the implementation of teaching, the field of competencies for evaluating teaching), the researcher processed the data using the weighted mean, the percentage weight, the Pearson correlation coefficient and the percentage. The results of the study showed that male and female first grade teachers possess teaching competencies with a weighted average for all fields of (2.28) and a percentage weight of (76.0). and distribution in an optimal manner) and recommendations, including (conducting workshops by university professors in basic education faculties for student teachers in schools in order to provide them with the necessary teaching competencies) and proposals including (conducting a comparative study of the necessary teaching competencies for male and female teachers between public schools and private schools ).